Kegiatan Pembelajaran Bahasa Indonesia Dalam Kurikulum Merdeka: Suatu Analisis Reflektif Berdasarkan Kebijakan Pendidikan - Kartini; Sintowati Rini Utami (STIT Muhammadiyah Paciran Lamongan, 2023)
The purpose of this study was to determine the reflective analysis of Indonesian language learning activities in the independent curriculum based on educational policies. The research method used is descriptive qualitative method. The type of data taken is a description of learning activities in the teaching module. The result of this study is that the learning activities in the independent curriculum teaching module are in accordance with existing policies and are based on life skills, namely life skills independently and in accordance with national education goals, namely on the spiritual dimension of faith, piety to God Almighty, and noble character as well as student participation in class.